Review on the role of social support in health information systems - Visvalingam A.; Dhillon J.S.; Gunasekaran S.S. (IEEE Computer Society, 2023)
Bioassay; Digital libraries; Health care; Information systems; Medical computing; Metadata; mHealth; Microarrays; Application developers; Cambridge university; Health informatics; Health information systems; Medical conditions; Mental health; Social support; Support systems; Information filtering